Chlorophyllin as a possible measure against vectors of human parasites and fish parasites - Richter, Peter R.; Strauch, Sebastian M.; Azizullah, Azizullah; Häder, Donat-P. (Frontiers in Environmental Science, 2014)
Water soluble chlorophyll (chlorophyllin) exerts pronounced photodynamic activity. Chlorophyllin is a potential remedy against mosquito larvae and aquatic stages in the life cycle of parasites as well as against ectoparasites in fish. In the recent years it was found that mosquito larvae and other pest organisms can be killed by means of photodynamic substances such as different porphyrin derivates (e.g. hematoporphyrin, meso-tri(N-methylpyridyl), meso-mono(N-tetra-decylpyridyl) porphyrine, hematoporphyrin IX, or hermatoporphyrin formula (HPF). It was found that incubation of mosquito larvae in chlorophyllin solution and subsequent irradiation results in photodynamic destruction of the larvae. Incorporation of about 8 ng chlorophyllin per larvae was sufficient to induce its death. In fish mass cultivation ichthyophthiriosis is a severe parasitic protozoan disease caused by the ciliate Ichthyophthirius multifiliis. It was found that incubation of infected fishes in chlorophyllin and subsequent illumination reduced the number of trophonts significantly (more than 50 %). The fishes were not impaired. Chlorophyllin and other photodynamic substances may become a possible countermeasure against I. multifiliis and other ectoparasites in aquaculture. The effectiveness of chlorophyllin depends on light attenuation in the water body.